2022
DOI: 10.1039/d2tb01146h
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic nano-coordination protein hydrogel for photothermal treatment and repair of infected skin injury

Abstract: In this work, a dynamic photothermal hydrogel based on copper disulfide nanoparticle and thiolated gelatin was reported. The resultant hydrogel enabled rapid photothermal sterilization and the sterilization rate could reach...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…After that, the HAP-Ag/PDA was cross-linked with 4-arm PEG-SH to form a hydrogel through a double-cross-linking system. First, the silver ions on HAP-Ag surface react with the sulfhydryl groups of 4-arm PEG-SH to form Ag–S dynamic coordination bonds. , Second, free quinone groups on HAP-Ag can also react with the sulfhydryl groups of 4-arm PEG-SH, which further enhances the mechanical properties of the hydrogel. Hence, DA modification enables HAP-Ag to be well distributed in the hydrogel network (Figure S1) and provides cross-linking sites for enhanced mechanical support.…”
Section: Resultsmentioning
confidence: 99%
“…After that, the HAP-Ag/PDA was cross-linked with 4-arm PEG-SH to form a hydrogel through a double-cross-linking system. First, the silver ions on HAP-Ag surface react with the sulfhydryl groups of 4-arm PEG-SH to form Ag–S dynamic coordination bonds. , Second, free quinone groups on HAP-Ag can also react with the sulfhydryl groups of 4-arm PEG-SH, which further enhances the mechanical properties of the hydrogel. Hence, DA modification enables HAP-Ag to be well distributed in the hydrogel network (Figure S1) and provides cross-linking sites for enhanced mechanical support.…”
Section: Resultsmentioning
confidence: 99%
“…The components of biofilms are complex. Bacteria are shielded by the extracellular matrix, which invalidates the host defense system and prevents antibiotics from contacting the encapsulated bacteria. In addition, it is easy for bacteria in the biofilm to mutate, accelerating the development of bacterial resistance . Therefore, it is paramount but challenging to prevent the formation of biofilms and kill mature biofilms that have been formed.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, PTT may be an effective way to kill bacteria and even drug-resistant strains without inducing drug resistance. Pan et al reported a dynamic photothermal hydrogel that enabled rapid photothermal sterilization to accelerate infected skin healing …”
Section: Results and Discussionmentioning
confidence: 99%
“…Pan et al reported a dynamic photothermal hydrogel that enabled rapid photothermal sterilization to accelerate infected skin healing. 46 Herein, we built a subcutaneous abscess model by infecting BALB/c mice with drug-resistant S. aureus (Figure 7A). GNR-DPArPEGMA was injected into the abscess site and imaged by a thermal infrared camera under 808 nm NIR laser irradiation for 3 min.…”
Section: Antibiofilm Activitymentioning
confidence: 99%